Live record of vortex-shaped flow by microgravity solidification. (1st November 2021) - Li, H.R.; Ruan, Y.
Graphical abstract: Highlights: Vortex microstructure reflecting the flow pattern formed. Marangoni convection affected the primary phase selection. Flow pattern was preserved during the rapid growth of metastable Ag2 Al dendrites. Microgravity solidification path changed with droplet size. Enhanced melt convection resulted in the increased vortex density. Abstract: A unique type of vortex-shaped microstructure reflecting the flow pattern during the microgravity solidification formed in Al70 Ag20 Ge10 alloy droplets using drop tube technique. A 2D axisymmetric model coupling heat transfer, fluid flow with phase change was established to simulate the fluid flow variation of alloy droplets during microgravity solidification. The Stokes motion was suppressed and the Marangoni motion was prominent in driving the vortex-shaped flow. The melt flow affected the phase selection, consequently the Ag2 Al phase nucleated primarily instead of (Al) phase under near-equilibrium solidification, and the flow pattern was preserved during the rapid growth of the metastable Ag2 Al dendrites. The Marangoni effect was weakened with the decrease of droplet size, and anomalous (Al) + Ag2 Al and intergranular (Al) + (Ge) eutectics formed owing to the enhanced nucleation and growth competition among phases. In comparison, Al70 Ag20 Ge10 alloy was solidified under gravity condition by DSC and vacuum arc melting methods respectively. No vortex-shaped microstructure formed in DSC sample ascribed to the suppressed natural convection at small cooling rate. During arc melting, the electromagnetic force and enhanced natural convection caused strong turbulent flow, the metastable Ag2 Al dendrites rapidly formed with increased vortex density.